Schülervorstellungen zur eisigen Welt der Polargebiete: Ergebnisse einer explorativ angelegten Studie - Conrad, Dominik (Zeitschrift für Geographiedidaktik (ZGD), 2012)
Polar Regions are used by scientists as early warning system of global climate change, and their significance in climate change science should be reflected in the geography curriculum. Taking a psychology approach, the research looked at mental models as a representation of pupils’ starting points of learning. To date few research results are available on pupils’ perceptions of the Polar Regions and the cryosphere. This explorative study focused on year eight pupils identifying their conceptions of the Arctic and Antarctic. A key finding was that pupils often have analogue conceptions of the Polar Regions in both hemispheres. Typical mental models included the existence of a huge is land, consisting of ice many hundred metres thick, icebergs as term to describe glaciers or seen as a relic of the last ice age and sea-level rising as a result of melting sea ice. These conceptions do not conform to existing scientific knowledge. This article presents the central results of the study and draws out implications and suggestions for associated changes in teaching. The article finishes with a proposed set of further research topics.